Incidence of chromosomal abnormalities in fetuses with first trimester ultrasound anomalies and a low‐risk cell‐free DNA test for common trisomies. (9th August 2020) - Persico, Nicola; Boito, Simona; Volpe, Paolo; Ischia, Benedetta; Gentile, Mattia; Ronzoni, Luisa; De Robertis, Valentina; Fabietti, Isabella; Olivieri, Claudiana; Periti, Enrico; Ficarella, Romina; Silipigni, Rosamaria; et al.
Abstract: Objective: To examine the incidence and type of chromosomal abnormalities in fetuses with first trimester ultrasound anomalies and a low‐risk cfDNA test for common trisomies. Methods: In 486 singleton pregnancies undergoing invasive testing after combined screening, a detailed first trimester ultrasound assessment was carried out and a maternal blood sample was sent for cfDNA analysis. Ultrasound and cfDNA data were analyzed in relation to fetal karyotype. Results: Invasive testing demonstrated a chromosomal abnormality in 157 (32.3%) of 486 fetuses. In 348 cases with a low‐risk cfDNA test for common trisomies, NT ≥ 3.5 mm and/or a major structural defect were observed in 92 (26.4%) fetuses. A chromosomal abnormality was found in 17 (18.5%; 95%CI 10.55‐26.41) of these pregnancies, including 1 (1.1%) case of trisomy 21 and 16 (17.4%) fetuses with abnormalities different from common trisomies. The respective incidence in the 256 cases with a low‐risk cfDNA test result and no ultrasound anomalies was 2.3% (95% CI 0.49‐4.20; n = 6). Conclusions: In fetuses with first trimester ultrasound anomalies and a low‐risk cfDNA result for trisomy 21, 18 and 13, diagnostic testing should be offered with the main objective to detect chromosomal abnormalities beyond common trisomies.